Arabic Teachers' Efforts in Developing Students' Vocabulary Mastery at MA Rasyidiyah Khalidiyah (Rakha) - Yanti, Rina; Zubaidillah , Muh. Haris; Nuruddaroini, M.Ahim Sulthan (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Mufradāt (vocabulary) is a fundamental component in Arabic language learning, serving as the basis for mastering listening, speaking, reading, and writing skills. However, students often face challenges in vocabulary mastery due to limitations in teaching methods, learning media, motivation, and the unique characteristics of the Arabic language. This study aims to describe the process of mufradāt learning, identify the challenges faced by students, and analyze teachers’ efforts to improve vocabulary mastery at MA Nipi Rakha.This research employed a qualitative descriptive approach, with data collected through classroom observations, in-depth interviews with Arabic teachers, and documentation. The findings reveal that mufradāt learning is implemented using various methods, including direct instruction, drilling, communicative approaches, language games, and contextual learning, supported by visual, audio, and concrete media.Despite these efforts, several challenges persist, such as students’ tendency to forget vocabulary due to lack of repetition, difficulties in pronouncing certain Arabic letters, differences in student abilities, and limited media variation. To address these issues, teachers simplify vocabulary load, provide special guidance, use concrete media, apply spaced repetition techniques, and enhance learning motivation. The study concludes that structured, varied, and continuous teacher efforts play a crucial role in improving students’ vocabulary mastery and overall success in Arabic language learning.